Modelos de crecimiento, digestion y lactancia en bovinos - Sainz, R.D.=700 1 Lee Baldwin, R.; Vernazza, R.F.
(En, Es)
ilus., 27 ref.
Keywords: MODELOS; CRECIMIENTO; DIGESTION; LACTANCIA; GANADO BOVINO; COLOMBIA